1979
DOI: 10.1007/bf00450227
|View full text |Cite
|
Sign up to set email alerts
|

Myositis ossificans following total knee replacement

Abstract: Two cases of myositis ossificans involving the quadriceps femoris muscle are described following total knee replacement arthroplasty. This condition appears to be a very rare complication of this operation. One case was helped by ultrasound therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…20 In 1975 Dahl 6 was the first to report on the effect of nonsteroidal anti-inflammatory drugs (NSAIDs) for prophylaxis against HO, and in 1981 Coventry and Scanlon 5 showed the efficiency of postoperative irradiation after hip replacements. In shoulder arthroplasty, as in elbow 10,14 or knee arthroplasty, 2,10,13,17,23 reports of HO are rare. Only two reports by Kjaersgard-Andersen et al 9 and Sperling et al 24 looked specifically for heterotopic bone formation after shoulder arthroplasty.…”
mentioning
confidence: 94%
“…20 In 1975 Dahl 6 was the first to report on the effect of nonsteroidal anti-inflammatory drugs (NSAIDs) for prophylaxis against HO, and in 1981 Coventry and Scanlon 5 showed the efficiency of postoperative irradiation after hip replacements. In shoulder arthroplasty, as in elbow 10,14 or knee arthroplasty, 2,10,13,17,23 reports of HO are rare. Only two reports by Kjaersgard-Andersen et al 9 and Sperling et al 24 looked specifically for heterotopic bone formation after shoulder arthroplasty.…”
mentioning
confidence: 94%
“…Booth et al [6] proposed that excessive bleeding might contribute to myositis ossificans following total knee arthroplasty. McClelland et al [5] also suggested that this may have been the case to a patient having postoperative bleeding due to warfarin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Encountered more commonly following total hip arthroplasty [4], only six cases have been reported in the English literature following knee arthroplasty [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous risk factors that have been listed for HO around the hip, such as previous history of HO, ankylosing spondylitis, Paget disease, hypertrophic osteoarthritis, and post-traumatic osteoarthritis characterized by extensive osteophytosis [3] , [4] , [10] , [11] , are also predisposing factors in TKAs. Other factors involved in the formation of HO after TKA are related to the surgical technique, such as excessive periosteal injury after exposure of the distal femur for instrumentation positioning, notching of the anterior cortex, damage to the quadriceps muscle, and inadequate hemostasis and knee hematoma [2] , [3] , [12] , [13] . Forced knee manipulation is also recognized as potentially increasing the risk factor [3] .…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of NSAIDS and local radiation therapy, in terms of prevention, has been studied and well documented for the hip [14] , [15] , and can also be applied for the knee [9] . Most knees with HO achieve a satisfactory clinical outcome without additional surgery [3] , [5] , [7] , [12] . Spontaneous resolution of pain with flexion restrictions has also been reported [6] .…”
Section: Discussionmentioning
confidence: 99%